Legal Criminal Policy Analysis Against Perpetrators in The Crime of Murder Under The Alcohol Influence - Bagaskoro, M. Rizal; Khumaeroh, Irda Nur (Jurnal Daulat Hukum, 2025)
Alcohol can cause intoxication (poisoning, numbing) of the brain. Drinks seem to cause psychoseacuut, with signs including euphorie (feeling great, happy), loss of moral control, lack of self-criticism, feeling great, trivialising danger, little concentration. This writing aims to know and understand the criminal policy towards the perpetrators of the crime of murder under the influence of alcohol and the form of criminal liability by the perpetrators of the crime of murder under the influence of alcohol. The research method used is normative juridical with statutory approach method. The results showed that the criminal policy against the perpetrators of the crime of murder influenced by liquor in force at this time, there is no provision that prohibits a person to drink liquor. Criminal responsibility by the perpetrator of the crime of murder influenced by alcohol can be held accountable for the perpetrator who deliberately brings himself into a state of intoxication (action libera in causa), with the intention of being more courageous in committing a crime.